Experimental assessment of pore fluid distribution and geomechanical changes in saline sandstone reservoirs during and after CO2 injection. (August 2017) - Falcon-Suarez, Ismael; Marín-Moreno, Héctor; Browning, Fraser; Lichtschlag, Anna; Robert, Katleen; North, Laurence J.; Best, Angus I.
Graphical abstract: Highlights: Experimental assessment of CO2 injection in shallow saline reservoir sandstones. Resistivity and P, S-waves are used to infer pore fluid distribution and pressure. Elastic geomechanical properties were analysed before and after CO2 exposure. Static and dynamic approaches are used to assess geomechanical changes. Aquifer recharge after CO2 injection may affect reservoir mechanical stability. Abstract: Responsible CO2 geosequestration requires a comprehensive assessment of the geomechanical integrity of saline reservoir formations during and after CO2 injection. We assessed the geomechanical effects of CO2 injection and post-injection aquifer recharge on weakly cemented, synthetic-sandstone (38% porosity) sample in the laboratory under dry and brine-saturated conditions, before and after subjecting the sample to variable pore pressure brine-CO2 flow-through tests (∼170 h). We measured ultrasonic P- and S-wave velocities ( Vp, Vs ) and attenuations, electrical resistivity and volumetric strain (ε v ). Vs was found to be an excellent indicator of mechanical deformation during CO2 injection; Vp gives mechanical and pore fluid distribution information, allowing quantification of the individual contribution of both phenomena when combined with resistivity. Abrupt strain recovery during imbibition suggests that aquifer recharge after ceasing CO2 injection might affect the geomechanical stability of the reservoir. Static and dynamic parameters indicate the sample experienced minor geomechanical changes during CO2 exposure, with an increase of Δε v < 3% and a drop in Δ Vs ∼1%. In contrast, due to brine-induced hydro-mechanical alteration, Δε v increased by ∼10% and Δ Vs by ∼6%. This study provides a multiparameter, thermo-hydro-mechanical-chemical database needed to validate monitoring tools and simulators, for prediction of the geomechanical behaviour of CO2 storage reservoirs.